Penerapan Strategi Marketing Lembaga Pendidikan Swasta di Era Industri 4.0: Studi Kasus di MA Al Amiriyyah - Zulvan Maulana; M. Luthfi Munir (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
The development of the era in the 21st century has entered an era where competition between educational institutions is increasingly competitive and requires educational institutions to adapt to developments in society. However, the public's interest in sending their children to school at MA Al Amiriyyah has not decreased. Seeing the phenomenon that occurred, researchers are interested in researching the implementation of marketing strategies for private educational institutions at MA Al Amiriyyah. The purpose of this study is to describe the implementation of marketing strategies for private educational institutions in the 4.0 era. This type of research is qualitative research using descriptive methods. Data collection techniques use observation and interviews. Data analysis methods use data reduction, data presentation and drawing conclusions. The results of this study indicate that of several marketing strategies for school institutions in the industrial era 4.0, they are more dominant in promoting through the internet and social media (websites, Instagram) and this is also shown in the results of parent interviews that school information is obtained through websites and social media.